Effect of temperature on the cumulative carbon loss from decaying copepod carcasses - Franco Cisterna, Belén; Stief, Peter; Glud, Ronnie N (PANGAEA, 2024)
The effect of varying temperature on the kinetics of aerobic microbial respiration (a proxy for oxidative carbon mineralization) associated with copepod carcasses was studied in laboratory incubation experiments. Copepod carcasses were produced by exposing female specimens of cultured Acartia tonsa to anoxic conditions for 2 hours. Carcasses were incubated in gas-tight glass vials equipped with an internal optode for contactless oxygen measurements at 5 different temperatures ranging between 4 and 20°C. Carcass-associated oxygen consumption was measured for varying time periods. The obtained respiration rates were converted to carbon mineralization rates using 3 different theoretical values for the respiratory quotient and 3 different theoretical values for bacterial production and then to the cumulative carbon loss relative to the initial carbon contents of the carcasses.
Keywords: Acartia tonsa; carbon loss; carcass; copepod; culture experiment; Laboratory experiment; Mineralization